Evaluating three methods to encourage mentally competent older adults to assess their driving behavior. Issue 1 (July 2015) - Uribe-Leitz, Tarsicio; Barmak, Lisa Allee; Park, Angela; Howland, Jonathan; Lee, Vonne; Lodato, Emma; Driscoll, Cassandra; Dechert, Tracey; Burke, Peter A.
Abstract : BACKGROUND: Fourteen percent (43.1 million) of the population in the United States was 65 years and older in 2012. This population is projected to reach 20% (88.5 million) by 2050. Older adults accounted for 17% of all traffic fatalities and 9% of all vehicle occupant injuries in 2012. We explored the effectiveness of three interventions to help older adults assess their current driving behaviors at a Level 1 trauma center. METHODS: During 2010 to 2012, 1, 216 inpatients 70 years and older admitted for surgical and medical services were screened for eligibility, and 120 were enrolled. Participants completed a driving assessment and preintervention questionnaires and were subsequently randomized to one of the following interventions: (1) brief negotiated interview plus an educational kit by the American Automobile Association about older driving plus an accompanying list of Web-based resources for older adult drivers; (2) American Automobile Association document and a list of Web-based resources; (3) online referral sheet of the list of Web-based resources only. A 3-month postintervention follow-up questionnaire was administered over the telephone to measure changes in (1) driving-related knowledge, attitudes, and beliefs as well as (2) driving-related behaviors and intended behaviors. RESULTS: A total of 113 randomized patients were included in the analysis. The mean (SD) age was 76.8 (5.23) years; majority of patients were white (64%), followed by black African American (33%); and 51% were males and 49% were females. Multivariate analysis showed that older adults' driving knowledge, attitudes, and beliefs ( p < 0.0001, R 2 = 0.37) as well as behaviors and intentions ( p < 0.0001, R 2 = 0.27) toward driving were positively correlated, controlling for other predictors in the model. Intervention assignment did not affect changes in outcomes, although outcomes improved across experimental conditions. CONCLUSION: Our pilot study suggests that older adults are likely to make changes in their driving behavior on the basis of minimal hospital-based intervention.